2018
DOI: 10.1259/bjr.20170655
|View full text |Cite
|
Sign up to set email alerts
|

Image quality comparison of two adaptive statistical iterative reconstruction (ASiR, ASiR-V) algorithms and filtered back projection in routine liver CT

Abstract: Both ASiR and ASiR-V improved the objective and subjective image quality for routine liver CT compared with FBP. ASiR-V provided further image quality improvement with higher acceptable percentage than ASiR, and ASiR-V60% had the highest image quality score. Advances in knowledge: (1) Both ASiR and ASiR-V significantly reduce image noise compared with conventional FBP reconstruction. (2) ASiR-V with 60 blending percentage provides the highest image quality score in routine liver CT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 16 publications
2
23
0
Order By: Relevance
“…Images were reconstructed using a new DL reconstruction TrueFidelity (TF) algorithm at low, medium and high strength, and a partial model-based iterative reconstruction (adaptive statistical iterative reconstruction-V, ASiR-V) at 60 % strength [19]. According to previous studies, ASiR-V 60 % was a superior algorithm compared to FBP, ASIR and other ASiR-V levels [34][35][36]. Based on this results and after a dedicated institutional optimization procedure, it was decided that 60 % ASiR-V was used in clinical routine for abdominal acquisitions.…”
Section: Experimental Design Image Acquisition and Reconstruction Protocolmentioning
confidence: 99%
“…Images were reconstructed using a new DL reconstruction TrueFidelity (TF) algorithm at low, medium and high strength, and a partial model-based iterative reconstruction (adaptive statistical iterative reconstruction-V, ASiR-V) at 60 % strength [19]. According to previous studies, ASiR-V 60 % was a superior algorithm compared to FBP, ASIR and other ASiR-V levels [34][35][36]. Based on this results and after a dedicated institutional optimization procedure, it was decided that 60 % ASiR-V was used in clinical routine for abdominal acquisitions.…”
Section: Experimental Design Image Acquisition and Reconstruction Protocolmentioning
confidence: 99%
“…[ 25 ] In the case of ASIR-V, blending with the traditional FBP was performed in 10% increments according to the user preference. [ 8 ] In previous reports comparing IR of different levels, [ 16 , 26 ] higher levels of IR induced exaggerated noise reduction, leading to excessive image smoothing or unnatural images compared with the FBP, which radiologists favor and are used to. Consequently, high level IR algorithms have limited usage in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…The DLIR can be done in 3 selectable strength levels (low, medium, and high), which varies in the degree of noise. [ 16 ] To the best of our knowledge, the effect of DLIR algorithms in abdominal CTs at different tube voltages and tube currents has yet to be evaluated. This is important because it may help optimize radiation doses in abdominal CT examinations which have the highest radiation dose compared with other types of CT scans.…”
Section: Introductionmentioning
confidence: 99%
“…Post-ASiR-V can significantly reduce the image noise and streak artifacts to improve image detail and quality. Previous studies have reported that post-ASiR-V with a higher percentage results in an improved image over smooth images, which affect the detection of small lesions [28][29][30] . Choosing an appropriate percentage of post-ASiR-V is therefore a key to maximizing image quality.…”
Section: Discussionmentioning
confidence: 99%